2018
DOI: 10.1166/jnn.2018.15472
|View full text |Cite
|
Sign up to set email alerts
|

Image of the Micro-Computed Tomography and Atomic-Force Microscopy of Bone in Osteoporosis Animal Model

Abstract: Osteoporosis, a major public health problem, is characterised by a reduction in and deterioration of bone tissue microarchitecture, with a consequent increase in bone frailty and susceptibility to fractures. We performed ex vivo micro-computed tomography (micro-CT) and atomic-force microscopy (AFM) between normal and surgically ovariectomized animals (OVX). The tibial architecture was investigated using maximum intensity projection images. Micro-CT analysis of the tibia metaphysis was used to calculate the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Osteoporotic‐like bones are characterized by the mineral resorption caused by increased osteoclasts activity that often reconfigure bone's microarchitecture. ( 3,13,46 ) Following the overall trend in this research, the proximal areas verified by AFM revealed a different appearance from those obtained from distal sites. The frequent and low amplitude peaks images found in the bones extracted from the proximal regions are characteristic from highly mineralized tissues.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Osteoporotic‐like bones are characterized by the mineral resorption caused by increased osteoclasts activity that often reconfigure bone's microarchitecture. ( 3,13,46 ) Following the overall trend in this research, the proximal areas verified by AFM revealed a different appearance from those obtained from distal sites. The frequent and low amplitude peaks images found in the bones extracted from the proximal regions are characteristic from highly mineralized tissues.…”
Section: Discussionsupporting
confidence: 62%
“…(12) The use of animal models has therefore been proposed. (13,14) anaesthetized individually in a 200 mL solution containing 70 ppm of Tricaine (MS-222;Sigma Aldrich; Missouri, MO, USA), adjusted to pH ~7.2 (± 0.1) with sodium hydroxide (NaOH), 130 µL of isoflurane (Alfa Aesar; Loughborough, Leicestershire, UK) and ethanol (isoflurane:ethanol = 1:9), as described elsewhere. (32) The anaesthetized fish were placed carefully onto a cell and tissue culture disk (Biofil; Kaohsiung, Taiwan) and the tiles images of the bright field (T-PMT-T3) and fluorescent light (Cy3-T3) of the caudal fin bony rays were taken with an inverted confocal microscope (LSM 800; Carl Zeiss, Oberkochen, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution MRI (HR-MRI) techniques can provide three-dimensional information about cancellous bone in peripheral regions with a resolution of the order of trabecular dimensions (in-plane resolution: ~ 110 μm, section thickness: ~ 300 μm) [7][8][9][10]. Recent advances also allow imaging of the proximal femur, a major area of clinical interest, although the signal-to-noise ratio (SNR) and resolution (in-plane resolution: ~ 250 μm, slice thickness: ~ 500 μm) are lower than peripheral areas [11].…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%